2016
DOI: 10.1007/s00421-016-3452-5
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and anti-inflammatory cytokine responses to a 164-km road cycle ride in a hot environment

Abstract: Completion of a 164-km cycling event induced substantial changes in circulating pro- and anti-inflammatory cytokine concentrations. Time to completion appears to have a greater influence on the systemic IL-10 response than the environmental condition; however, it is possible that a threshold for absolute intensity must be reached for environmental conditions to affect the IL-10 response to exercise. Thus, cyclists from the FAST/MOD groups appear more likely to experience an acute transient immune suppression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…High intense interval training (HIIT) is able to promote lymphocyte oxidative stress and reduce super antigen-induced proliferation [ 35 ]. Long-distance running is able to increase the number of circulating total leukocytes with the increase in neutrophils, monocytes, and lymphocytes including B and T cells [ 36 ]. Therefore, it has been suggested that exercise represents a physical stress that is able to modify the counting of immune cells in the peripheral blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…High intense interval training (HIIT) is able to promote lymphocyte oxidative stress and reduce super antigen-induced proliferation [ 35 ]. Long-distance running is able to increase the number of circulating total leukocytes with the increase in neutrophils, monocytes, and lymphocytes including B and T cells [ 36 ]. Therefore, it has been suggested that exercise represents a physical stress that is able to modify the counting of immune cells in the peripheral blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has spent considerable effort examining the relationship between exercise recovery and inflammation ( McFarlin et al, 2006 , 2007 , 2016 ; Luk et al, 2016 ; Tanner et al, 2020a , b ). The findings of the present study further the existing knowledge regarding post-exercise DAMP signaling/inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…55 Recent evidence suggests that high intensity exercise can induce oxidative stress 34 and inflammation. 7,13,36 after exercise. Our study, also showed that during a short exercise of high intensity (100%) the inflammatory factors CRP, IL-6, TNF-α increase, as well as APN and TAC, which is in accordance with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is well documented that acute exercise increases expression and circulating levels of many inflammatory molecules such as cytokines and chemokines. [2][3][4][5][6][7][8] Tumour necrosis factor α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP) are cytokines that have pro-inflammatory effects; on the other hand, adiponectin (APN) and interleukin-10 (IL-10) are cytokines with anti-inflammatory effects. Acute training increases muscle production of IL-6 which is responsible for reducing pro-inflammatory TNF-α and increasing anti-inflammatory cytokines, such as APN.…”
Section: Introductionmentioning
confidence: 99%